Beltrania-like Taxa from Thailand - Chuan Gen Lin (2018)
© 2017 Adac. Four Beltrania-like taxa, viz., Beltrania rhombica, Beltraniella fertilis, Beltraniopsis longiconidiophora sp. nov. and Hemibeltrania cinnamomi were identified during a survey of hyphomycetes in Thailand. Each species is provided with a description and a molecular analysis. The new species is introduced based on morphological and molecular differences and compared with similar taxa. Beltraniella fertilis and H. cinnamomi are new records for Thailand.